Revitalisasi Pembelajaran Bahasa Arab: Pendekatan Integratif Berbasis CTL, Cooperative Learning, dan PAKEM untuk Meningkatkan Minat Belajar Siswa - Ali Musyafak; Kholidin, Afif; Iin Nihayatun Naimah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze the underlying causes of low interest in Arabic language learning and to formulate pedagogical solutions through the integration of Contextual Teaching and Learning (CTL), Cooperative Learning, and the PAKEM (Active, Creative, Effective, and Joyful Learning) framework. Adopting a descriptive qualitative approach with a library research method, this study critically analyzes data to identify epistemological, affective, and pedagogical barriers in Arabic instruction, while exploring the potential interventions of the three aforementioned strategies.The findings indicate that the decline in student interest is primarily driven by material abstraction, language anxiety, and passive instructional methods. The integration of these three strategies offers a complementary and holistic solution: CTL addresses cognitive barriers by contextualizing material into meaningful learning experiences; Cooperative Learning mitigates affective obstacles by fostering psychological safety through peer support; and PAKEM overcomes motoric-engagement barriers by stimulating joyful, active participation. The synergy of these strategies effectively shifts the instructional paradigm from passive-instructional to active-participatory, fundamentally reconstructing and enhancing student engagement and interest in Arabic language acquisition.